Research on the Impact of Delayed Retirement Policy on the Labor-market Under the Background of Population Aging - Dong, Shuangyu (Transactions on Social Science, Education and Humanities Research, 2025)
On a global scale, population aging has become a serious issue that cannot be ignored. The challenges it brings, such as labor shortage and increased burden of elderly care, have prompted governments around the world to actively seek solutions. Delaying retirement policies is one of the most concerned measures. In this context, this article focuses on the Chinese labor market, deeply analyzes its overview and current situation, meticulously studies the multidimensional impact of delayed retirement policies on the labor market, and emphasizes the importance of implementing delayed retirement policies. The research results indicate that the delayed retirement policy has had complex and far-reaching impacts on the Chinese labor market. In the short term, this policy can effectively increase the number of workers in the labor market and inject vitality into economic development; However, from a long-term perspective, the lack of supporting policy measures will exacerbate the structural contradictions in the labor market and affect the sustainable development of the economy and society.